Communal Wastewater Treatment Plant Planning to Support The Concept of Eco-Boarding Schools in NU Al-Mansyuriah Islamic Boarding Schools, Central Lombok Regency - Gagassage De Side (ITB Journal Publisher, LPPM ITB, 2021)
A technical study of WWTP planning is carried out in the context of developing Islamic boarding schools with the concept of Eco-Boarding School, covering aspects such as waste water collection facilities, processing facilities, and socio-economic aspects of the surrounding land. Technical aspects of development planning with a communal system will be investigated in determining the wastewater treatment system and planning for the development of wastewater infrastructure. The method used is to study literature and literature, as well as field observations, to gain an overview of the problem from the location and appropriate technical aspects to obtain primary data. Primary data in the form of direct observations, waste water quality data, clean water quality data, topographic data, and secondary data in the form of student enrollment and village population data. Analysis of wastewater generation discharge, determination of wastewater treatment capacity, formulation of alternative wastewater treatment technologies, and determination of WWTP locations can all be performed using these data. This sanitation facility planning produces a wastewater treatment plant design in the form of a Detailed Engineering Design. Based on the findings of an analysis of the projected number of residents of Islamic boarding schools and the forecast of wastewater services for the next 20 years, the volume of wastewater generation is up to 0.96 m3/day, and the results of the scoring analysis for determining the location of the WWTPs, the alternative locations can be accepted with a score of 305. Communal WWTPs are located at coordinates 8°47'0.43